THE GOVERNANCE OF UNIVERSITY EDUCATIONAL ENDOWMENT FUND IN INDONESIA - Jepri Walistian, (Juremi: Jurnal Riset Ekonomi, 2025)
This study explores the governance of university educational endowment funds in Indonesia as a long-term strategy to ensure the sustainability of higher education institutions. While endowment fund practices are well-established in developed countries, implementation in Indonesia faces key challenges, including limited regulatory frameworks, low investment literacy, and continued dependence on government funding. Using a qualitative descriptive approach and financial report analysis of universities with endowment funds, the research examines reporting structures, asset allocations, and investment performance and risks. The findings highlight the importance of transparent governance frameworks, diversified investment strategies, and active stakeholder engagement. Comparative analysis with international best practices reveals the need for institutional capacity building and policy enhancement. The study recommends cross-sector collaboration, professional asset management, and greater involvement from alumni and the private sector in strengthening endowment funds. These insights offer strategic guidance for universities and policymakers aiming to build long-term financial resilience and enhance the quality of higher education in Indonesia.